Tolerance to oxidative stress is required for maximal xylem colonization by the xylem‐limited bacterial phytopathogen, Xylella fastidiosa. (25th August 2016) - Wang, Peng; Lee, Yunho; Igo, Michele M.; Roper, M. Caroline
Summary: Bacterial plant pathogens often encounter reactive oxygen species (ROS) during host invasion. In foliar bacterial pathogens, multiple regulatory proteins are involved in the sensing of oxidative stress and the activation of the expression of antioxidant genes. However, it is unclear whether xylem‐limited bacteria, such as Xylella fastidiosa, experience oxidative stress during the colonization of plants. Examination of the X . fastidiosa genome uncovered only one homologue of oxidative stress regulatory proteins, OxyR. Here, a knockout mutation in the X . fastidiosa oxyR gene was constructed; the resulting strain was significantly more sensitive to hydrogen peroxide (H2 O2 ) relative to the wild‐type. In addition, during early stages of grapevine infection, the survival rate was 1000‐fold lower for the oxyR mutant than for the wild‐type. This supports the hypothesis that grapevine xylem represents an oxidative environment and that X. fastidiosa must overcome this challenge to achieve maximal xylem colonization. Finally, the oxyR mutant exhibited reduced surface attachment and cell–cell aggregation and was defective in biofilm maturation, suggesting that ROS could be a potential environmental cue stimulating biofilm development during the early stages of host colonization.